RNA-seq profiling reveals differentially expressed genes as potential markers for vital reaction in skin contusion: a pilot study - Jingtao Xu; Rui Zhao; Ye Xue; Huanqin Xiao; Yanliang Sheng; Dong Zhao; Jietao He; Hongyan Huang; Qi Wang; Huijun Wang (Oxford University Press, 2018)
Detection of the vitality of wounds is essential in forensic practice. The present study used Illumina RNA-seq technology to determine gene expression profiles in contused mouse skin. In obtained high quality sequencing reads, the reads were mapped onto a reference transcriptome (Mus_musculus.GRCm38.83). The results revealed that there were 659 up-regulated and 996 down-regulated differentially expressed genes (DEGs) in contused mouse skin. The DEGs were further analyzed using the Gene Ontology and the Kyoto Encyclopedia of Genes and Genomes databases. Genes from different functional categories and signalling pathways were enriched, including the immune system process, immune response, defense response, cytokine-cytokine receptor interaction, complement and coagulation cascades and chemokine signalling pathway. Expression patterns of 11 DEGs were verified by RT-qPCR in mice skins. In addition, alterations of five DEGs were also analyzed in postmortem human wound samples. The results were in concordance with the results of RNA-seq. These findings suggest that RNA-seq is a powerful tool to reveal DEGs as potential markers for vital reaction in terms of forensic practices.